Comparação entre sistemas de comunicação digital operando com monoportadora e multiportadoras/OFDM sob canal com multipercursos e efeito Doppler - Fonseca Neto, João (2013)
In digital mobile communication systems, in which signals are transmitted via radio, multipath distortions manifest themselves as a linear intersymbol interference, ISI, because of multiple copies of the same signal arriving at the receiver with different time delays. To combat the effects of ISI, one of the tools used is Orthogonal Frequency-Division Multiplexing, OFDM. OFDM is a modulation technique that employs simultaneously several subcarriers which have been successfully used in both wired communication systems and in radio transmission systems. It has been especially used in the transmission of signals in digital mobile systems with high data rates through a communication channel with multipath, noisy, with severe frequency selective fading, because as one of the most important characteristics of this technique is to have great resistance to ISI and ICI, even in adverse conditions. The objective of this work is to present a comparative study of the behavior of digital communication systems operating with single carrier and multicarrier OFDM in Rayleigh channel, particularly considering the achievements of Doppler shift and multipath. The study is based on simulation, from the perspective of performance, through analysis of bit error rate curves, BER versus Eb=N0.